Sequência didática como instrumento para a mobilização das capacidades de linguagem no ensino da produção do gênero artigo de opinião - Lima, Elisandro Félix de (2023)
In this project work, the aim is to demonstrate the importance of the didactics sequence, inspired by geneva, as a fundamental instrument to promote language skills in the process of teaching the production of the opinion article genre. We started from the necessity to raise a theoretical and methodological basis of the procedures of the device didactic sequence, in order to contribute to the continuing education of teachers who work directly with the teaching leveling of Portuguese language, in the full-time school program, in the state of Rondônia. In that way, through this investigation, we tried to answer what is the importance of the didactic sequence in the context of Portuguese language teaching and, specifically, how it can be used to mobilize language skills in the process of teaching the production of the opinion article genre. The research is guided by studies of Sociodiscursive Interactionism and Applied Linguistics, in particular on language skills as aptitudes required in the process of receiving and producing texts textual genres as language teaching objects and didactics sequences as a set of practical activities, ordered and linked together to achieve certain learning objectives. For this, we rely on theorists who discuss these topics: Bronckart (2006); Bakhtin (2016); Marcuschi (2010); Gondim (2012); Cristovao (2013); Costa-Hübes and Simioni (2014); Dolz, Pasquier and Bronckart (2017); Dolz, Noverraz and Schneuwly (2004); Casseb-Galvão and Duarte (2018) among others. As a methodology, in addition to a bibliographical study regarding the didactic sequence device, genre textual teaching and language skills, we elaborated a didactic sequence so that the organized activities could mobilize the essential language skills for the production of the opinion article genre. To analyze this procedure, we developed a chart to demonstrate how the teacher can promote the mobilization of language skills in the process of writing teaching, through the didactic sequence instrument. Our results showed that in relation to the action of teaching the essay of the opinion article genre, the didactic sequence, inspired by Geneva, can be an excellent tool for planning and organizing activities, since, as it is a long-term resource, , can favor the deepening of the content to be taught, in addition, this procedure proves to be essential to promote the development of language skills in situations of reception and production of texts. Finally, we hope that these results can contribute to the scientific advance in the area of Applied Linguistics and that they help as an inspiration for the introduction of new studies on the subject, mainly, by the teachers who participate in the teaching of leveling Portuguese language in the state of Rondônia